Nanoporous TiO solar cells sensitised with a fluorene–thiophene 2 copolymer - Ravirajan, P.; Haque, S.A.; Poplavskyy, D.; Durrant, J.R.; Bradley, D.D.C.; Nelson, J. (University of Jaffna, 2004)
Composites of nanostructured metal oxides with conjugated polymers are promising material combinations for efficient solar energy conversion.However, performance of such combinations is normally limited by the low interfacial area of planar structures and poor charge carrier mobility of the polymer.In this study, we focus on TiO with a high hole-mobility polymer, poly (9,99- 2 dioctylfluorene-co-bithiophene) (F8T2).Transient optical spectroscopy confirms that efficient photo-induced electron transfer occurs from F8T2 to TiO in both planar TiO yF8T2 structures and in high surface area, porous TiO yF8T2 structures. 2 2 2 Recombination between the positive polaron in the polymer and electron in the TiO is remarkably slow (;ms) in both cases. 2 The influence of layer thickness and surface morphology on cell performance was examined.The best cell was made with reduced layer thickness and increased surface morphology and offered an external quantum efficiency of 11.5% and monochromatic power efficiency of 1 at.% 440 nm. This cell produced an open circuit voltage Voc of 0.80 V and a short circuit current density of approximately 300 mAycm under simulated air mass (AM) 1.5 illumination. However, the power conversion efficiency is 2 limited by a poor fill factor, which is attributed to an energy barrier at the polymerymetal interface.We investigate this problem using alternative polymer and top contact metals. 2003 Elsevier B.V. All rights reserved.
Keywords: Solar cells; Nanostructure; Titanium dioxide; Thiophene; Polymer; Electrodes